2008
DOI: 10.1097/pas.0b013e31816380ec
|View full text |Cite
|
Sign up to set email alerts
|

Basaloid Squamous Cell Carcinoma of the Head and Neck is a Mixed Variant That Can be Further Resolved by HPV Status

Abstract: Basaloid squamous cell carcinoma (BSCC) of the head and neck is set apart as a distinct subtype of squamous cell carcinoma on the basis of its basaloid appearance and aggressive behavior. The purpose of this study was to determine whether BSCC could be further subdivided on the basis of human papillomavirus 16 (HPV16) status. HPV16 in situ hybridization was performed on 53 BSCCs of the head and neck. Of the 53 BSCCs, 21 (40%) arose in the oropharynx and 32 (60%) arose in nonoropharyngeal sites. HPV16 was detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
201
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 209 publications
(212 citation statements)
references
References 28 publications
7
201
0
2
Order By: Relevance
“…Some studies have shown no association of HPV/p16 expression with basaloid squamous cell carcinoma, whereas other recent studies have suggested that HPV may be present and accompanied by strong p16 expression, especially in basaloid squamous cell carcinoma of the oropharynx. [22][23][24][25] It is also important to keep in mind that strong and diffuse p16 staining can occur in adenoid cystic carcinoma, even in the absence of co-existing HPV infection, and focal p16 expression is extremely common in these tumors. Lastly, although p16 overexpression is often used as a surrogate marker for HPV infection in squamous cell carcinoma, it cannot be used in this manner in high-grade adenoid cystic carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown no association of HPV/p16 expression with basaloid squamous cell carcinoma, whereas other recent studies have suggested that HPV may be present and accompanied by strong p16 expression, especially in basaloid squamous cell carcinoma of the oropharynx. [22][23][24][25] It is also important to keep in mind that strong and diffuse p16 staining can occur in adenoid cystic carcinoma, even in the absence of co-existing HPV infection, and focal p16 expression is extremely common in these tumors. Lastly, although p16 overexpression is often used as a surrogate marker for HPV infection in squamous cell carcinoma, it cannot be used in this manner in high-grade adenoid cystic carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Although they appeared to do well clinically, the number of cases is too small to make any meaningful conclusions. Several histologic variants of SCC, including nonkeratinizing SCC, basaloid SCC, papillary SCC, and undifferentiated carcinoma [7][8][9][10], have been shown to harbor high risk HPV when arising in the oropharynx. Papillary SCC, in particular, can have transcriptionally-active HPV in nonoropharyngeal locations such as the larynx [9].…”
Section: Discussionmentioning
confidence: 99%
“…These tumors may present as different variants distinct from the typical keratinizingtype SCC, including nonkeratinizing [5,6], basaloid [7,8], and papillary SCC [9] and also undifferentiated carcinoma [10]. It has also been documented in several studies that HPV-related carcinomas of the upper aerodigestive tract have more favorable prognosis than HPV negative ones [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Also, all major studies that performed multivariate survival analysis to control for other variables have found that positive p16 IHC independently correlates with better survival [2,5,6,9,12]. In particular, it is also prognostically independent of the histologic features of the SCC [22], such as keratinizing versus nonkeratinizing types (unpublished data), and, for most, if not all, specifically-defined SCC variants arising in the oropharynx, such as basaloid SCC [23], undifferentiated carcinoma [24], and adenosquamous carcinoma [25].…”
Section: Introductionmentioning
confidence: 95%